2022
DOI: 10.1002/emp2.12608
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an algorithm‐based care pathway for patients with non‐valvular atrial fibrillation presenting to the emergency department

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Five studies improved guideline adherence through antibiotic prescribing guidelines 46 , 80–82 or medical calculators. 83 Masica et al 84 embedded voluntary medical calculators and showed a decrease in hospital admissions. Ramnarayan et al 49 improve documentation quality through a diagnostic support system.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies improved guideline adherence through antibiotic prescribing guidelines 46 , 80–82 or medical calculators. 83 Masica et al 84 embedded voluntary medical calculators and showed a decrease in hospital admissions. Ramnarayan et al 49 improve documentation quality through a diagnostic support system.…”
Section: Resultsmentioning
confidence: 99%
“…7,9 Similar to previous studies evaluating different AF treatment pathways in the ED, the utilisation of the AF pathway described in the present study reduced the rate of hospital admission by 30.1% (a net 13.1%). 6,21 Despite the significant reduction in hospitalisation, AFrelated representation and all-cause mortality rates were similar between the two groups, positioning the AF pathway as a safe alternative to early cardioversion and/or inpatient management of acute uncomplicated symptomatic AF/AFL. Furthermore, implementation of this AF treatment strategy likely leads to significant savings by reducing the costs associated with unnecessary cardioversions, avoidable hospitalisations and their potential complications.…”
Section: Discussionmentioning
confidence: 96%